2018
DOI: 10.18805/lr-3731
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sowing dates, mulching and seed rates on nutrient uptake and productivity of soybean in sub - humid Punjab, India

Abstract: A field experiment was conducted for three years to study the effect of sowing dates, mulching and seed rates on nutrient uptake and productivity of soybean under irrigated conditions in sub-humid Punjab on a silty clay loam soil which was low in available N, medium in available P and available K. The experiment was conducted in a split plot design with the combination of three sowing dates and mulch in main plots and three seed rates in sub-plots with three replications on fixed site. The results revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
1
4
0
Order By: Relevance
“…Enhancement in soybean growth under minimum tillage with residue treatment might be due the reason that the soil water was conserved and used for soybean growth rather than evaporation. Similar results were found by Sikka et al (2018) in soybean. They reported that plant height tended to increase with the application of wheat straw mulch over no mulch treatment.…”
Section: Resultssupporting
confidence: 90%
“…Enhancement in soybean growth under minimum tillage with residue treatment might be due the reason that the soil water was conserved and used for soybean growth rather than evaporation. Similar results were found by Sikka et al (2018) in soybean. They reported that plant height tended to increase with the application of wheat straw mulch over no mulch treatment.…”
Section: Resultssupporting
confidence: 90%
“…The number of pods/plant and seed yield were found to be significantly highest at the lower seed rate for faba bean and recorded significantly lowest at the highest plant density (Wakweya & Meleta, 2016). Similarly, Sikka et al (2018) reported that the number of pods/plant significantly decreased in soybean at a higher seed rate because of the competition for space, water, sunlight and plant nutrient.…”
Section: Effects Of Seed Rate On the Yield Of Egusi Melonmentioning
confidence: 92%
“…However, they concluded that grain accumulation of N, P, K, and S was not influenced by seed rate or spacing. A three year study suggested that the maximum total uptake of nutrients in soybean is under higher seed rate i.e., intense spacing [30].…”
Section: Nutrient Uptakementioning
confidence: 99%